If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7y = 6 + -8y Solving 3 + -7y = 6 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 3 + -7y + 8y = 6 + -8y + 8y Combine like terms: -7y + 8y = 1y 3 + 1y = 6 + -8y + 8y Combine like terms: -8y + 8y = 0 3 + 1y = 6 + 0 3 + 1y = 6 Add '-3' to each side of the equation. 3 + -3 + 1y = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 6 + -3 1y = 6 + -3 Combine like terms: 6 + -3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| -64=-8(p+1) | | X(x-48)=180 | | 12+12n=-48 | | -2x+12=0 | | 11/12t-3/4t=5/6 | | -1/7(7y+5) | | 1+6x=97 | | -2+12=0 | | x/2+14 | | 2(x+8)+3x=7+2x | | 9y-(6y+19)=6-(3y-4) | | 15-2x=3y | | 6x-8=6(x+7) | | -4y-11=4r+21 | | 0=7(a+1) | | (y^2-6y+8)/(y^2+3y-28) | | -7x-10=53 | | 5p+12=2t | | 3-2B+B+4+B=57 | | 138-x=45 | | -2x+4=-3 | | -9-3(2m-1)=-18 | | 9y+x=8 | | 75+45x=255 | | -5=-6+b/3 | | 120-4(8x-22)=16 | | x+x+54=90 | | 2x+1/5=3x+2/5 | | 15=50 | | 5(-1+-1y)+y=-13 | | 5(-1+-1y)+y=-31 | | 9x^2-6x+37=0 |